Organising Transregional Child Protection within the Greater Region of France, Germany, Belgium and Luxembourg - Christian Schröder; Ulrike Zöller (Social Work and Society)
Within the framework of the Interreg project EUR&QUA we investigated the transnational organisation of child protection in the Greater Region. The basis of our research has been a transregional perspective. The concept of the transregional draws its creative potential from the thematisation of border crossings and the critical examination of all forms of container thinking and essentialisation. We have analysed interviews with professionals as well as with families involved in these cross-border placements. Our main focus has been on the participation rights of children concerning the organisational processing of children across borders within the Greater Region. The impact of cross-border placements within the Greater Region on children, their parents, their siblings and the child and youth welfare organisations involved in two countries are still largely unknown. Against the background of our research, we consider transregional placements to be useful only in exceptional cases, namely when they are based on a rights-based approach.